Implementasi Program Pemberdayaan Masyarakat Desa (P2md) Di Dinas Pemberdayaan Masyarakat Desa Kabupaten Kepulauan Selayar - Ahmad Ahmad; Abdul Mahsyar; Anwar Parawangi (Kolaborasi : Jurnal Administrasi Publik, 2021)
AbstractThis study aims to determine the context of implementing the Village Community Empowerment Program (P2MD). The type of research used is descriptive qualitative research. The data is collected through interviews with key informants in turn, direct observation at the target location of the program and official government documents such as legislation and program implementation guidelines issued by the central government and local governments. The data obtained was processed directly by connecting the themes. The results showed that the involvement of the actors involved in the implementation of the program was based on the applicable regulatory provisions related to the program established by the related institutions. On another aspect, the characteristics of the government involved range from the central government to the village government. As for the non-governmental institutions that are formally involved, there is no other than community groups that act as both the executor and target of the empowerment program. The compliance of the parties involved as implementing the community empowerment program is going well. Substantial and administrative performance achievements according to targets in planning.Keywords: Program Implementation, Village Community Empowerment